the -6 is smaller and above the u. the 2 is outside the parentheses and smaller.
the -6 is smaller and above the u. the 2 is outside the parentheses and smaller.
Given that the expression you're trying to simplify looks like this --- (u^{-6})^{2} --- here's how I would start to tackle it.
Expression: (u^{-6})^{2
}Multiply the exponents: u^{-12
}
Then, it's important to know that u^{-1 }= 1/u
When you apply that to the expression you are working with, it looks like this:
Flip expression to remove negative exponent: 1/u^{12}
Hi Angela!
You could simply but surely "type out" the expression:
u^-1= 1/u ==> u^-6= 1/(u*u*u*u*u*u), now squaring this thing means you'll have twice as many u's ...
Since (1/u)^2= (1/u)(1/u) ==> (1/u^6)(1/u^6)= 1/(u^12) Best wishes, ma'am :)